Elaboración de un manual de procesos administrativo para el departamento de obras públicas del Gobierno Autónomo Descentralizado del Cantón Bolívar. - Almeida Vélez, María Inés (2016)
The research aimed to design an administrative manual for the public works department of the Autonomous Government Decentralized Canton Bolivar to improve its management, having as objective the identification and diagnosis of processes and activities carried out in this department, and the development of the administrative manual. the interview, which consisted of a dialogue with the principal, where he said he has eight employees in charge, and said, that do not have a manual process was applied, but it would be essential to implement to optimize time in the development of activities , through the results it was identified in the public works department six fundamental processes are developed; execution of works, supervision, permits for construction, surveying, repair machinery, and reception and settlement of the work. The diagnosis allowed to know that some of the servers run activities that do not concern you, for example drafted the minutes of receipt of the work: it is among the activities director, but who runs it is the assistant, ie do not have a written document to see the activities that have to play in the development of their work. It is concluded that the manual process proposed is designed in an orderly, clear and easy to use, to improve process development department, which allows the institution through its servers provide quality service to its citizens , contributing to the progress of the canton.